KARAKTERISTIK DAERAH TANGKAPAN AIR SUNGAI MALALAYANG SULAWESI UTARA - Marcel J. R. Ratag; Johny S. Tasirin; Alfonsius Thomas (Universitas Sam Ratulangi, 2015)
ABSTRACTTHE CHARACTERISTIC CATCHMENT AREA OF MALALAYANG RIVER NORTH SULAWESIThis research aim to identify the characteristics catchment area of Malalayang river. This research was done from february until march 2012 at catchment area of Malalayang river. The methods in this research is doing by observations to the area to verification and collect the data in some sample representative area. Sample point observable are in Air Panas catchment area, Warembungan catchment area and Tomohon catchment area. This research show the closure of the land in sub watershed Malalayang is dominated by estate mixed with broad area 2941.95ha, settlement population 583.11ha, forest area 534.18ha, grass area 306.3ha, field area 190.92ha and free area 71.55ha. the speed of water in Air Panas catchment area 234.0 m3/hour, the speed of water in Warembungan catchment area 831.6 m3/hour and the speed of water in Tomohon catchment area 882.0 m3/hour. The result of the regression equivalen is y = 0.217x + 339.59 with r2= 0.5107.Key words; water catchment area, land over, water discharge